2018
DOI: 10.1093/jme/tjy090
|View full text |Cite
|
Sign up to set email alerts
|

Pest Cockroaches May Overcome Environmental Restriction Due to Anthropization

Abstract: Our species have altered their surroundings since its early dispersion on Earth. Unfortunately, thanks to human-modified habitats, several pest organisms such as domiciliary insects have expanded their distributions. Moreover, pest-related microorganisms may also be aided by anthropization. Pest cockroaches are globally distributed and capable of carrying several diseases. We explored if urbanization may buffer environmental conditions allowing pest insects to expand their distribution. Specifically, we sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The urban microhabitat features unique climatic regimes, photoperiod and resource availability. In response to these selective pressures, successful synanthropic animals including cockroaches [4], rats [5] and crows [6] exhibit many behaviours absent in non-urbanized sibling species. Understanding these behaviours is of major importance to public health.…”
Section: Introductionmentioning
confidence: 99%
“…The urban microhabitat features unique climatic regimes, photoperiod and resource availability. In response to these selective pressures, successful synanthropic animals including cockroaches [4], rats [5] and crows [6] exhibit many behaviours absent in non-urbanized sibling species. Understanding these behaviours is of major importance to public health.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these species correspond to worldwide distributed synanthropic species, where most research on medical entomology has been focused (Nasirian 2019; Schapheer et al . 2018). For instance, the general biology, urban ecology and pathogenic associations of P. americana (Kassiri & Kazemi 2012; Yoon et al .…”
Section: Discussionmentioning
confidence: 99%
“…The generalized prevalence of pest cockroaches we found in Quetta should be considered as a public health concern by the relevant authorities and decisions makers in Pakistan and abroad (Greene & Breisch 2002; Krieger & Higgins 2002; Schapheer et al . 2018). This may become especially important when the world is still battling a global pandemic, and knowing that cockroaches are capable of contributing to the transmission of nosocomial infections (Fakoorziba et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations from the field in both native and invaded ranges show that P. dominula appear to preferentially nest near human habitation (Höcherl andTautz 2015, Roets et al 2019). This pattern of synanthropy is seen in related species (Parent et al 2020) and has been shown to allow other taxa to invade regions where environmental conditions are unsuitable (Schapheer et al 2018). Additional modelling including human habitation and land-use as variables may be able to produce a more realistic prediction of P. dominula potential range.…”
Section: Discussionmentioning
confidence: 86%